Unlocking sustained business value from IT investments - Peppard, Joe; Ward, John (University of California, 2005)
Surveys continue to highlight that most senior business executives are dissatisfied with the value they believe their organizations are deriving from investments in information technology. What is often forgotten is that IT in itself has no inherent value. This value must be unlocked, and only business executives and users can do this. While most IT investments are usually accompanied by a technology implementation plan, few organizations ever construct a plan focused on realizing the business benefits. This article explores how organizations can unlock business value from their IT investments by adopting a two-stage view of implementation. This model distinguishes between "problem-based" interventions and "innovation-based" interventions. Unlocking business value from IT investments is a journey not a destination and this journey requires careful planning.
Keywords: Information technology; Innovation adoption; Investment policy; Value; Business planning; Management science; Customer relations management; Problem based learning